Particle physics : a very short introduction - Close, F. E. (Oxford ; New York : Oxford University Press, 2004)
Beginning with a guide to what matter is and what it is made of this book discusses everything from quarks and electrons to exotic matter and antimatter. The author concludes by speculating as to the number of dimensions that might be in the universe, and what the next 50 years of research might uncover.
Journey to the centre of the universe -- How big and small are big and small? -- How we learn what things are made of, and what we found -- The heart of the matter -- Accelerators : cosmic and manmade -- Detectors : cameras and time machines -- The forces of Nature -- Exotic matter (and antimatter) -- Where has matter come from? -- Questions for the 21st century.
Includes bibliographical references (pages 131-132) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Particles (Nuclear physics) -- Popular works; Particules (Physique nucléaire) -- Ouvrages de vulgarisation; SCIENCE -- Physics -- Nuclear; SCIENCE -- Physics -- Atomic & Molecular; Particles (Nuclear physics); Partículas (física nuclear); Particles (Nuclear physics); Electronic books; Popular works